Transient switch-on collector current analysis in punch-through IGBT - Islam, Md. Akhirul; Hossain, MD. Nazmul; Altab, M. Mubaswir; Bhowmik, Tonmoy (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.